Change in Lung Volume Following Thoracoscopic Anterior Spinal Fusion Surgery: A 3-Dimensional Computed Tomography Investigation. Issue 12 (15th June 2017) - Yu, Caroline G.; Grant, Caroline A.; Izatt, Maree T.; Labrom, Robert D.; Askin, Geoffrey N.; Adam, Clayton J.; Little, J. Paige
Abstract : Study Design: Lung volumes and thoracic anatomy were measured from low-dose computed tomography (CT) scans preoperatively and 2 years following thoracoscopic anterior spinal fusion (TASF) for adolescent idiopathic scoliosis (AIS). Objective: The aim of this study was to assess changes in lung volume after TASF surgical correction. Summary of Background Data: AIS patients are known to have decreased pulmonary function as a consequence of their spinal and ribcage deformity. Several studies have evaluated changes in pulmonary function clinically after scoliosis correction surgery showing varied results. To date, there have been no published studies using CT to evaluate lung volume changes following TASF. Methods: Twenty-three female AIS patients with both pre- and 2 years postoperative low-dose CT scans were selected from an ethically approved, historical databank. Three-dimensional lung volumes were reconstructed to determine anatomical lung volumes. Right and left lung volumes, total lung volume, and right-to-left lung volume ratio were obtained as well as hemithoracic symmetry, to indicate the extent of thorax deformity. Cobb angle, rib hump, levels fused in surgery, and patient height were used for correlation analysis with the lung volume results. Results: Left lung volume, total lung volume, and hemithoracic ratio all increased significantly 2 years after surgery. There was no significant change in right-to-left lung volume ratio ( P  = 0.36). Statistical regression found significant positive correlation between lung volume changes, reduction in Cobb angle, increase in height, and improvement in hemithoracic symmetry ratio. Conclusion: TASF resulted in a statistically significant increase in lung volume following surgery, as well as improvement in the symmetry of the thoracic architecture; however, the postoperative lung volumes remained in the lower 50th percentile relative to females without thoracic deformity. Furthermore, change in lung volume was significantly correlated with changes in Cobb angle, hemithoracic asymmetry, and increased patient height, which are important consequences of thoracic deformity correction surgery. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text